USE OF LEARNING MEDIA ICT-BASED TO IMPROVE MOTIVATION AND THE RESULT OF LEARNING SCIENCE IN SOLAR SYSTEM MATERIALS - Fitriani, Fitriani; Hidayatulloh, Rezza Munari Fatah; Agra, Hana Sakura Putu (COLLASE (Creative of Learning Students Elementary Education), 2018)
This research raises the problem of the low motivation and learning outcomes of science in the sixth grade students of SDN 257 Pelita, Kecamatan Lengkong, Bandung City. The objectives of this study are as follows: (1) To find out the improvement of science learning motivation through the use of ICT-based learning media. (2) To determine the increase in science learning outcomes using ICT-based learning media This type of research is Classroom Action Research (CAR) with a model developed by Kemmis and McTaggart. The subjects of this study were 30 students. The results showed that. (1) the use of ICT-based learning media can improve learning motivation. This can be seen from the increase in the average student motivation increases. (2) The use of ICT-based learning media can improve learning outcomes. This can be seen from the average value of student learning outcomes increases with the results of the percentage of non-compliance increased.